Induction of Viable but Nonculturable Escherichia coli O157:H7 by Low Temperature and Its Resuscitation - Wei, Caijiao; Zhao, Xihong (Frontiers in Microbiology, 2018)
Viable but non-culturable (VBNC) cells are alive bacteria cells, but lose their culturability in conventional culture media, usually escape detection by the plate count method and pose a serious threat to food safety and public health. Therefore, it is urgent to study the VBNC status, and to provide theoretical basis and scientific basis for food processing and safety control caused by pathogenic microorganisms. In this study, Escherichia coli O157:H7 was induced to the VBNC state at two different temperatures (-20°C and 4°C) and its resuscitation and morphological changes under different nutritional conditions were studied. The initial inoculum of 2.1 × 107 CFU/mL E. coli O157:H7 cells were induced into the VBNC state in normal saline, distilled water, LB broth at -20 °C after 176, 160, 80 days, respectively. The results showed that E. coli O157:H7 reserved at -20°C, and LB culture medium were easier to enter VBNC state than others conditions, the cells still had metabolic activity and the cell morphology changed from the typical rod shape to short rod and the cell size decreased. The resuscitate ways including the direct warming resuscitation, gradual warming resuscitation, adding chemical substance resuscitation, and adding nutrients resuscitation were studied. The results showed that the optimal conditions of 5% Tween 80 and 3% Tween 80 acculated the resuscitation of E. coli O157:H7 VBNC state cells induced by low temperature LB medium and low temperature saline. E. coli O157:H7 VBNC state failed from resuscitation when incubating in LB broth, respectively using direct warming and adding nutrients substance. This study provides new insights into induction and resuscitation of VBNC E. coli O157:H7 and offers an approach for investigating the formation mechanism of VBNC foodborne pathogens in food safety.